Analisis Strategi Pemasaran Sebagai Upaya Peningkatan Penjualan Pakaian Menggunakan Analitycal Hierarchy Process - Tanisri, Roberta H. A.; Rizarahman, Hafizh; Suminar, Ratna; Nadia, Ainun (Program Studi Teknik Industri, Fakultas Teknik, Universitas Bhayangkara Jakarta Raya, 2023)
Alya Clothing Store has been selling clothing products since it was first established in 2020. During these two years there have been ups and downs in the process of selling clothing products as an effort to make a profit. The evaluation was carried out in 2022 where in that year there was a decline in sales which had an impact on the decline in store turnover. This study aims to help the management of Alya Clothing Store make the most appropriate marketing strategy in the current situation. The method used in this research is to approach Analitycal Hierarchy Process (AHP) analysis. Data processing is done by mapping using SWOT analysis, where internal factors (strengths and weaknesses) and external factors (opportunities and threats) can be known precisely. Based on the SWOT analysis, the Alya Clothing Shop is located in the 4th quarter, namely the diversification condition. The four alternative strategies obtained are narrowed down to one strategy with AHP analysis, which is to focus on improving service quality in terms of security, environmental cleanliness and friendliness of service to visitors.